2012
DOI: 10.1080/00379271.2012.10697748
|View full text |Cite
|
Sign up to set email alerts
|

Relation entre facteurs environnementaux et densités larvaires d’Ochlerotatus caspiusPallas 1771 etOchlerotatus detritusHaliday 1833 (Diptera: Culicidae) en Tunisie

Abstract: Abstract. Relationship between environmental factors and larval density in Ochlerotatus caspius Pallas 1771 and Ochlerotatus detritus Haliday 1833 (Diptera: Culicidae) of Tunisia. Ochlerotatus caspius and Oc. detritus, two major mosquito species considered as pests in Tunisia, are subjected to intensive insecticide treatments. Considering the large areas colonized by immature stages and high adult densities generated at each egg hatching period, the effi ciency of insecticide control is limited. In order to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Surprisingly, AN mosquitoes were characterized by a delay in RVFV transmission; AN populations were more likely to transmit 21 days after feeding on an infectious blood-meal (see Figure 4F ). We suggested that epizootic outbreaks of RVF can be initiated by Aedes or Ochlerotatus mosquitoes which are present in high densities in rural areas [14] , [44] , [45] . Aedes mosquitoes such as Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, AN mosquitoes were characterized by a delay in RVFV transmission; AN populations were more likely to transmit 21 days after feeding on an infectious blood-meal (see Figure 4F ). We suggested that epizootic outbreaks of RVF can be initiated by Aedes or Ochlerotatus mosquitoes which are present in high densities in rural areas [14] , [44] , [45] . Aedes mosquitoes such as Ae.…”
Section: Discussionmentioning
confidence: 99%